2014
DOI: 10.1155/2014/381413
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Protective Effect ofPhysalis peruvianaL. against Carbon Tetrachloride-Induced Hepatotoxicity in Rats Is Mediated by Suppression of Oxidative Stress and Downregulation of MMP-9 Expression

Abstract: The active constituent profile in Cape gooseberry (Physalis peruviana L.) juice was determined by GC-MS. Quercetin and kaempferol were active components in the juice. In this study we have evaluated its potential protective effect on hepatic injury and fibrosis induced by carbon tetrachloride (CCl4). Twenty-eight rats divided into 4 groups: Group I served as control group, and Group II received weekly i.p. injection of 2 mL CCl4/kg bwt for 12 weeks. Group III were supplemented with Physalis juice via the drink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 49 publications
8
50
0
2
Order By: Relevance
“…Additionally, the observed increase in alterations to liver enzymes, including ALT, AST and ALP, in HCCreceived CHJ rats may be due to the improvement of the functional status of hepatocytes with preservation of cellular architecture leakage of intracellular enzymes through membrane-stabilizing activity. [18,53] Previous studies have suggested that CGJ is a significant source of natural antioxidative compounds.…”
Section: [42]mentioning
confidence: 99%
“…Additionally, the observed increase in alterations to liver enzymes, including ALT, AST and ALP, in HCCreceived CHJ rats may be due to the improvement of the functional status of hepatocytes with preservation of cellular architecture leakage of intracellular enzymes through membrane-stabilizing activity. [18,53] Previous studies have suggested that CGJ is a significant source of natural antioxidative compounds.…”
Section: [42]mentioning
confidence: 99%
“…Concentrations of Cd in an adjacent environment is cumulative owing to its miscellaneous sources and very long biological half-life ranging from 10 to 30 years. Cd in biological systems is dispensable and it is known to be toxic even at low concentrations [2][3]. Cadmium exposure (acute and chronic) in plants, animals, and humans may cause harm to various organs, including the brain, gastro-intestinal tract, liver, lungs, and testes.…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium exposure (acute and chronic) in plants, animals, and humans may cause harm to various organs, including the brain, gastro-intestinal tract, liver, lungs, and testes. Many related disorders include renal dysfunction, hepatotoxicity, anemia, osteoporosis, DNA damage, neurodegenerative diseases, and immunosuppressive and proinflammatory effects [3][4][5][6]. A number of mechanisms have been proposed to explain the damage induced by Cd, but it is not yet well understood, although some experimental evidence can determine that deleterious effects of cadmium are due to oxidative stress by depletion of the endogenous antioxidants that serve as a premier source of protection against free radicals and other oxidative stressors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies has been conducted to test health properties of Physalis peruviana L plant, cape gooseberry and calyx, concluding to a potential association of intakes with in vitro and in vivo anti-inflammatory activity [25,26], inhibition of TPA-induced (12-O-tetradecanoylphorbol-13-acetate) oedema in mice [27], effectiveness in decreasing cadmium toxicity in rats [28,8,29], hepatoprotective, renoprotective and cholesterol suppression effects [8,[30][31][32][33][34], antidiabetic and antihypertension activity [35][36][37][38][39] and cytotoxic activity against in vitro non-specific cancer cells [40] and lung cancer cells [41]. These potential health benefits are associated with the presence of phytochemicals in the extracts such as withanolides, physalins, vitamin C, flavonoids and phenolics, among others.…”
Section: Fruit and Vegetables Phytochemicals And Health Propertiesmentioning
confidence: 99%